YouTube as an Innovative Tool for Enhancing English Listening Skills in EFL Students - Khafida, Zahrotul; Marisa, Alina Nurul; Salwa, Inamul Maidatus (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study aims to see how YouTube works as an innovative tool to help improve English listening skills among students who learn English as a foreign language. The research was done at UIN K.H. Abdurrahman Wahid Pekalongan and involved two students from the English Education program as participants. The main focus of this study is how students use YouTube to practice listening outside of class time and how they view the effectiveness of the platform. Data were collected through semi-structured interviews that allowed participants to share their experiences in more detail. Thematic analysis was used to find the main patterns in the data. The results show that YouTube gives easy access to different English sources and helps students hear real English in various accents, speaking speeds, and real-life situations. The participants said that watching YouTube regularly helped them improve their vocabulary, pronunciation awareness, and overall listening skills. YouTube also supports independent learning by letting students choose content based on their interests and language level, which makes the learning process more fun and personal. However, the study also found some challenges, such as difficulty staying focused and choosing the right videos. Overall, this research shows that YouTube can be a useful extra resource to help EFL students improve their listening skills outside the classroom. It also highlights the need for guidance in using digital media effectively to support independent learning.